The CURE assessment landscape from the instructor’s point of view: knowledge and skills assessments are highly valued support tools for CURE adoption - Kleinschmit, Adam J.; Govindan, Brinda; Larson, Jennifer R.; Qureshi, Amber A.; Bascom-Slack, Carol (Frontiers in Education, 2023)
Course-based undergraduate research experiences (CUREs) are a high-impact educational practice that engage students with authentic research in the classroom. CURE development models include those designed and implemented at individual institutions to wide-reaching multi-institutional network CUREs. The latter have lowered barriers to implementation by providing a centralized support system, centralized training and curricula, and mentoring. CURE learning outcomes span the three domains of learning: knowledge, skills, and attitude. Assessment of these domains can serve a variety of purposes to a collection of different stakeholders. To better understand the CURE assessment landscape from the instructor’s point of view we surveyed instructors from an established network CURE. We found that these instructors, particularly those from associate’s colleges, overwhelmingly prefer use of knowledge and skills-based assessments over attitudinal CURE assessment instruments. Instructors value knowledge and skills assessment data when deciding whether to adopt a particular CURE and for identifying student misconceptions to improve CURE instruction, and for documentation necessary for Community College transfer agreements or for gaining approval from curriculum committees. CURE learning models have pointed toward use of generalizable instruments for measuring CURE outcomes, but since knowledge and skills assessments are typically CURE specific, obtaining funds for their development may not be realistic. To address this concern, we outline a CURE network stakeholder co-design process for developing and validating a knowledge and skills assessment instrument without external support or a sizable time commitment. We encourage network CUREs to leverage their communities to generate and validate knowledge and skills assessment instruments to further lower barriers for instructor adoption.